2019
DOI: 10.1177/0264550519859067
|View full text |Cite
|
Sign up to set email alerts
|

A model of a specialist transitional support and liaison service within the Offender Personality Disorder Pathway in Wales: Learning from a regional pilot service

Abstract: The process of transitioning from custody to the community can be a time of increased risk of reoffending and heightened anxiety brought on by uncertainty of future plans and unfamiliarity of new surroundings. This period can be particularly problematic for those experiencing complex needs or suffering with mental health difficulties. To address this concern, the Offender Personality Disorder Pathway (OPDP) in Wales established a Transitional Support Liaison service. This pilot service began with a focus on wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…It may be possible to draw parallels between our findings and those previously identified in relation to offenders accessing other relevant psychological services (Adamson et al, 2013; Brooker and Glyn, 2012; Brooker et al, 2012: Byng et al, 2012; NOMS, 2014; O’Meara et al, 2019; Ramsden et al, 2016; Scott and Moffatt, 2012; Skett et al, 2017). For example, The Centre for Mental Health briefing issued in 2012 in relation to the MHTR 3 for offenders acknowledged that the MHTR accounts for under 1% of requirement ordered despite the prevalence of mental health diagnosis amongst the probation population (approximately 39–40% of the population) (Brooker and Glyn, 2012).…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…It may be possible to draw parallels between our findings and those previously identified in relation to offenders accessing other relevant psychological services (Adamson et al, 2013; Brooker and Glyn, 2012; Brooker et al, 2012: Byng et al, 2012; NOMS, 2014; O’Meara et al, 2019; Ramsden et al, 2016; Scott and Moffatt, 2012; Skett et al, 2017). For example, The Centre for Mental Health briefing issued in 2012 in relation to the MHTR 3 for offenders acknowledged that the MHTR accounts for under 1% of requirement ordered despite the prevalence of mental health diagnosis amongst the probation population (approximately 39–40% of the population) (Brooker and Glyn, 2012).…”
Section: Resultssupporting
confidence: 79%
“…Reasons for this identified include instability within their lives following release from prison, instability in relational family support, financial difficulties and other difficulties in accessing services (Byng et al, 2012; Scott and Moffatt, 2012). Similarly, recent research conducted within the pathway (O’Meara et al, 2019) and in the Improving Access to Psychological Therapies (IAPT) practice guidance relating to offenders (Adamson et al, 2013) have indicated offenders within the probation services continue to be underrepresented within psychological services in the community. Barriers to engagement in appropriate community services again appear consistent with some of the offender barriers to engagement in IIRMS raised in the current study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations